Comparison of efficacy and cost-effectiveness of BIOMIC VIDEO and Vitek antimicrobial susceptibility test systems for use in the clinical microbiology laboratory. - Berke, I (1996)
Antimicrobial susceptibility testing expense may be a significant portion of a clinical microbiology laboratory's budget. This study compares the BIOMIC VIDEO system (Giles Scientific, Inc., New York, N.Y.) with the Vitek system (bioMérieux Vitek, Inc., Hazelwood, Mo.), an established automated method of antimicrobial susceptibility testing with the ability to generate MIC data. The BIOMIC system is relatively inexpensive and automates the reading of the classical disk agar diffusion test to provide both qualitative (susceptibility interpretation) and quantitative (MIC) data. The overall MIC correlation between the two systems for the 2,913 drug-organism combinations tested was 92.6%. The overall agreement for susceptibility interpretation was 97.4%. The BIOMIC system offers a 57.4% savings per test over the Vitek system. The BIOMIC system utilizes an older technology which is more efficient and yet yields results comparable to those of established automated MIC methods. The savings achievable in laboratories and hospitals nationwide may contribute significantly to the containment of national health care expenditures.